Засадничі принципи правотворчої діяльності як основа її ефективності - Плавич, В.П.; Плавич, С.В. (Альманах права, 2012)
В статті досліджено природу, функціонування та розвиток основних (засадничих) принципів правотворчої діяльності. Показано, що принципи правотворчості є тими засадами, на яких стверджується цілеспрямована та ґрунтовна робота по створенню правових норм, перспектив розвитку не тільки права, а й суспільства і держави. В статье исследовано природу, функционирование и развитие основных принципов правотворческой деятельности. Показано, что принципы правотворчества являются теми основами, на которых утверждаются целенаправленная и основательная работа по созданию правовых норм, перспектив развития не только права, а и общества и государства. The article explored the nature, functioning and development of the basic (fundamental) principles of law making activities. It is shown that the principles of lawmaking principles are the ones that allegedly targeted and substantial work on the creation of legal norms, perspectives of not only rights but also society and the State. The most fundamental principle of lawmaking on the modern stage of nation-building is the principle of the rule of law. All, without exception, actions of subjects of law-making activities occur under authority of legislation and within the overall constitutional norms. Herewith defining the concept of legitimacy used its lawmaking activity in general and special sense. In the first case comes to compliance with the general law-making constitutional principle of democratic and legal state( that is this laws and other normative-legal acts shouldn’t contrary to the spirit of constitutionally established rights and freedoms of human and citizen, encroach on State and public order, border of management, etc). However, the principle of legality in the activities of the lawmaking in a narrow (special) sense is on the front of the observance of legislative procedure (order of development, discussion, adoption and promulgation of the regulations), as well as adherence to the hierarchy of legal acts. Legality is a universal principle and addressed as to law — makers as to measures. Taking into account the priority directions of State policy on the modern stage of euro integration processes considered it necessary to highlight on our opinion, undoubtedly an important principle-the principle of international priority, since international law is integral to the domestic legal system. Harmonization of the legal system of Ukraine with the norms and standards of international law related to the amplification in the world integration processes. Implementation of the priority of international law in legal practice in Ukraine requires first and foremost improving legislation, which should provide a mechanism for the implementation of international legal standards in the legal system of Ukraine. The following security is not only domestic but also international legal responsibility of the State. Based on the analysis of the fundamental principles of law-making activity, it becomes apparent that law-making is based on the following basic principles that are commonly accepted the essence of the activity, its characteristics and basic directions. Such principles are : 1) the rule of law; 2) democracy; 3) scientific; 4) the legality; 5) professionalism; 6) humanism; 7) international priority. The implementation of these principles in the law making activity contributes to its effectiveness and improvement in terms of compliance with law, social feasibility of normative-legal acts that are accepted and their classification, as well as principles of data directly affect social development, democratic, legal State.